Identification of Eight Small Nucleolar RNAs as Survival Biomarkers and Their Clinical Significance in Gastric Cancer - Wang, Xuning; Xu, Maolin; Yan, Yongfeng; Kuang, Yanshen; Li, Peng; Zheng, Wei; Liu, Hongyi; Jia, Baoqing (Frontiers in Oncology, 2019)
Gastric cancer is one of most common cancers worldwide. Studies have shown that small nucleolar RNAs(snoRNAs) play important roles in several cancers. In this study, we analyzed the snoRNAs that were differentially expressed between gastric tumors and normal tissues, identified survival-associated snoRNAs, and developed an eight-snoRNA signature to predict overall survival of patients with gastric cancer. Furthermore, we explored the clinical significance of the eight signature snoRNAs. The risk biomarker established by the eight snoRNA signature was an independent prognostic factor (hazard ratio = 3.43, 95% confidence interval: 1.93 - 6.09, P = 2.72e-05). Furthermore, we validated the expression pattern of those snoRNAs in different gastric cancer cell lines and 5 paired normal and tumor tissues by using real time quantification PCR. Knocking down U66, one of the eight snoRNAs, inhibited the cell proliferation. In conclusion, we identified an eight-snoRNA risk signature to predict overall survival of gastric cancer patients. Seven of these snoRNAs were associated with clinical features of the disease. Knocking down U66 inhibited cell proliferation. These findings provide new clues with prognostic and therapeutic implications in gastric cancer.